STRATEGIC UNCERTAINTY AND ENVIRONMENTAL SCANNING: THE CASE FOR INSTITUTIONAL INFLUENCES ON SCANNING BEHAVIOR - ELENKOV, DETELIN S. (Strategic Management Journal, 1997)
This study examined the relationship between perceptions of strategic uncertainty and environmental scanning behaviors. It has been postulated that the strength of this relationship will depend on the combined effect of the environmental constraints and the prevailing approach to strategic decision making. A sample of 141 medium-size Bulgarian companies, all of them operating in a highly constrained external environment and a business culture, characterized by a low degree of calculative strategic decision making, was used to test four hypotheses related to scanning behavior. The empirical findings of this study were then compared with the results of prior research on environmental scanning in the United States in order to draw conclusions for both the theory of scanning behavior and strategic management practice in various environments. © 1997 by John Wiley & Sons, Ltd.